Relationship between Body Mass Index and Blood Pressure Level in Hypertensive Patients Attending Kiambu District Hospital, Kenya - Mbijiwe, Jane; Chege, Peter; Munyaka, Ann (International Journal of Health Sciences & Research, 2017)
Uncontrolled hypertension is the primary cause of cardiovascular disease occurrence which greatly contributes to fatality worldwide. Obesity is known to impact cardiovascular health, being an appropriate predictor of blood pressure. Many hypertensive patients have been found to be obese across the world. Scarce information exists on the relationship between obesity and blood pressure level among hypertensive patients. This research aimed at assessing the body mass index of hypertensive patients in a developing country. The study was conducted on a sample of 134 hypertensive patients attending Kiambu District Hospital in Kenya. Cross-sectional analytical research design was adopted and respondents selected using systematic sampling method. Anthropometric parameters of weight and height were used to assess body mass index. A pretested questionnaire was used to collect data from the respondents. Data was analyzed by use of statistical package for social science. The respondent’s body mass index was described by use of descriptive statistics. The relationship between blood pressure level and body mass index was determined by use of Pearson correlation test. A p-value of <0.05 was used as criterion for statistical significance. The study population had high body mass index as revealed by the high prevalence of overweight and obesity at 82.9%. Of the 134 respondents, 79.1% had uncontrolled blood pressure. Positive significant relationship was found between body mass index and blood pressure (r=0.683, p<0.001). Based on these findings, measures that would lead to healthy body mass index among hypertensive patients should be put in place for better hypertension management.
Keywords: Body mass index; hypertension; overweight; obesity